Collecting recipes: Byzantine and Jewish pharmacology in dialogue - Lehmhaus, Lennart ca. 20./21. Jh.; Martelli, Matteo (Science, technology, and medicine in ancient cultures, 2017)
"This volume brings together contributions covering different periods of the history of ancient pharmacology and medical writing, from Greek, Byzantine, and Syriac medicine to the Rabbinic-Talmudic medical discourses. It highlights the overwhelming mass of information about drugs and remedies in classical and late-antique sources, and traces the transmission and transformation of pharmacological knowledge across cultural and linguistic boundaries"--